METODE FILSAFAT DALAM TINJAUAN ILMU AGAMA - Abdullah, M. Amin (Jurnal Bestari, 1991)
Vienna Circle may be considered as a embrio of logical positivism. In general, positivism itself could notbe separated from the noted French philoshoper; August Comte. He was the leading scholar who taught positive stage of though as the highest conclusion of man adventure. In the modern world, however, positive thinking is not enough to solve men?s problems. The inner aspects of life usually does not need positive thinking solely. In many cases, they need to be resolved by religion.